AAssessment of participatory budgets in a medium-sized city in Spain: reviewing models, building indicators and learning from the experience (Revista Iberoamericana de Estudios Municipales, 2023)
After 30 years of Participatory Budgets (PBs) in cities around the world, there have been many experiments and few assessments. But, how to evaluate an experience of participatory budgeting without own assessment model? The purpose of this work is to assess the PB of the Spanish city of Zaragoza using a model developed by the researchers themselves. The method involved a synthetic model to assess the practical case with empirical information obtained through the techniques of direct observation, structured interview and analysis of secondary sources. The results bring significant innovations: the inclusion in the model of an area related to the design and planning of the participatory process, which allowed to incorporate contingent variables that demonstrated the dynamism of the process. The outcomes contribute the measuring of 105 indicators grouped into 35 scopes, 15 criteria and four spheres. The result was a positive, medium-high, assessment of the experience. This model is simple and flexible, and could be used to evaluate other experiences in intermediate cities.
Keywords: Participatory Budgeting; assessment; Citizen Participation; synthetic model